2007
DOI: 10.1021/mp060070y
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidate Pronucleotides:  A Comparison of the Phosphoramidase Substrate Specificity of Human and Escherichia coli Histidine Triad Nucleotide Binding Proteins

Abstract: To facilitate the delivery of nucleotide-based therapeutics to cells and tissues, a variety of pronucleotide approaches have been developed. Our laboratory and others have demonstrated that nucleoside phosphoramidates can be activated intracellularly to the corresponding 5'-monophosphate nucleotide and that histidine triad nucleotide binding proteins (Hints) are potentially responsible for their bioactivation. Hints are conserved and ubiquitous enzymes that hydrolyze phosphoramidate bonds between nucleoside 5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
195
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(201 citation statements)
references
References 44 publications
6
195
0
Order By: Relevance
“…It has been demonstrated for the phosphoramidase activity of Hint-1 that the enzyme prefers purine-based substrates rather than pyrimidines and that a hydroxyl group at the ribose 2Ј position of the substrate is essential for interactions with the ␥-oxygen of Asp-43 (rHint-1) of the enzyme in the binding pocket (45). We observed a similar tendency for rHint-1 desulfurating activity.…”
supporting
confidence: 69%
“…It has been demonstrated for the phosphoramidase activity of Hint-1 that the enzyme prefers purine-based substrates rather than pyrimidines and that a hydroxyl group at the ribose 2Ј position of the substrate is essential for interactions with the ␥-oxygen of Asp-43 (rHint-1) of the enzyme in the binding pocket (45). We observed a similar tendency for rHint-1 desulfurating activity.…”
supporting
confidence: 69%
“…Because binding of PSI-352707 to Hint1 was very weak, we were not able to determine the kinetic parameters for PSI-352707 with this enzyme (K m Ͼ1 mM). Chou et al (21) have studied Hint1 substrate specificity using different phosphoramidates and phosphoramidothiolates, and the reported K m values ranged from 0.13 to 215 M. The weak binding affinity for PSI-352707 may be due to the 2Ј-fluoro-2Ј-methyl disubstitution on the sugar moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Because Hint proteins have been shown to possess phosphoramidase activity (15,21,22), recombinant human Hint1 and Hint3 were cloned, purified, and tested for the ability to convert PSI-352707 to the corresponding monophosphate, PSI-7411. The activity of purified Hint1 and Hint3 was first tested with the control compound AMP-NH 2 , and both enzymes were able to deaminate AMP-NH 2 to AMP (data not shown).…”
Section: Conversion Of Psi-352707 To Psi-7411 By Hintmentioning
confidence: 99%
“…It was then subjected to chromatography on a SiO 2 gel column; the product was eluted with CHCl 3 /MeOH/ H 2 O (5:3:0.5). The relevant fractions were concentrated in vacuo, the residue was dissolved in water (1 ml) and lyophilized to afford the title compound as a white solid (14 mg, yield 14%); 1 kinetic studies were carried out with tryptamine 5Ј-adenosine phosphoramidate (TpAd) or AIPA as substrate and with the fluorescent activity assay as described (5). Excitation wavelength was set at 280 nm, fluorescence emission was measured at 360 nm, and excitation and emission slits were set at 10 nm for concentrations of substrates ranging from 0.05 to 1 M for wild-type and 5 nm for concentrations ranging from 10 to 50 M for V97D, V97E, and V97R mutants.…”
Section: Methodsmentioning
confidence: 99%
“…Hints are homodimeric proteins that have been found to be purine phosphoramidases (2)(3)(4)(5). Recently, we have demonstrated that lysyl-adenylate (lysyl-AMP) generated by bacterial and human lysyl-tRNA synthetases (LysRS) are also substrates for the respective bacterial and human Hints (6).…”
mentioning
confidence: 99%